Star of Persia : Esther's story - Smith, Jill Eileen, 1958- (Revell, a division of Baker Publishing Group, 2020)
"Esther is poised to save her people from annihilation. Relying on a fragile trust in a silent God, can she pit her wisdom against a vicious enemy and win?" --